Pharmacological interventions for the prevention of relapse in bipolar disorder: a systematic review of controlled trials. - Beynon, S; Soares-Weiser, K; Woolacott, N; Duffy, S; Geddes, J (2009)
We conducted a systematic review and meta-analysis of randomised and quasi-randomised controlled trials evaluating all clinically relevant pharmacological interventions for the prevention of relapse in people with bipolar disorder. Thirty-four trials were included in the review. Direct comparisons with placebo and with lithium were available for most drugs. In addition, there were direct comparisons of valproate vs. olanzapine, imipramine vs. lithium plus imipramine, olanzapine plus mood stabilisers vs. mood stabilisers and perphenazine plus mood stabilisers vs. mood stabilisers. Methodological quality varied across studies and the strength of evidence was not equal for all treatments or for all comparisons. There is evidence from placebo-controlled trials for the efficacy of lithium, valproate and lamotrigine as maintenance therapy for the prevention of relapse in bipolar disorder. Three drugs have a significant effect in the prevention of manic relapses (lithium, olanzapine and aripiprazole) and three in the prevention of depressive symptoms (valproate, lamotrigine and imipramine). Imipramine is little used in practice, because of concern about adverse effects. The significant effects of olanzapine and aripiprazole were demonstrated in selected responsive bipolar I patients only. Despite widespread use in clinical practice, there is little evidence to support the efficacy of combination therapy.